2012
DOI: 10.1007/s11205-012-0099-4
|View full text |Cite
|
Sign up to set email alerts
|

The Multidimensionality of Welfare State Attitudes: A European Cross-National Study

Abstract: When evaluating the various aspects of the welfare state, people assess some aspects more positively than others. Following a multidimensional approach, this study systematically argues for a framework composed of seven dimensions of the welfare state, which are subject to the opinions of the public. Using confirmatory factor analyses, this conceptual framework of multidimensional welfare attitudes was tested on cross-national data from 22 countries participating in the 2008 European Social Survey. According t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
162
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(172 citation statements)
references
References 27 publications
3
162
0
7
Order By: Relevance
“…The independent variables are aligned with the hypotheses and with findings in previous studies, which have found them to be significant determinants of social attitudes concerning the role of government in social provision (Algan, Cahuc, and Sangnier 2011;Foster and Kaminska 2012;Roosma, Gelissen, and van Oorschot 2013;Schwander and Häusermann 2013), in redistribution (Jaeger 2009;León 2012;Stegmueller et al 2012), in government measures to promote equality, security, and opportunity (Taylor-Gooby 2011).…”
Section: Variablessupporting
confidence: 83%
“…The independent variables are aligned with the hypotheses and with findings in previous studies, which have found them to be significant determinants of social attitudes concerning the role of government in social provision (Algan, Cahuc, and Sangnier 2011;Foster and Kaminska 2012;Roosma, Gelissen, and van Oorschot 2013;Schwander and Häusermann 2013), in redistribution (Jaeger 2009;León 2012;Stegmueller et al 2012), in government measures to promote equality, security, and opportunity (Taylor-Gooby 2011).…”
Section: Variablessupporting
confidence: 83%
“…These studies all find large proportions of populations perceiving overuse of welfare benefits (Ervasti, 1998(Ervasti, , 2012Goul Andersen, 1999;Halvorsen, 2002). In European comparative studies that analyze attitudes toward a broad range of welfare dimensions, perceived overuse is often standing in stark contrast to mostly positive perceptions of social programs and social rights (Roosma et al, 2012;Sihvo and Uusitalo, 1995a;Svallfors, 1991;Van Oorschot and Meuleman, 2011). Moreover, in studies in which overuse is analyzed as part of other critical welfare attitudes -for example, the bureaucracy of the welfare state or the idea that welfare makes people lazy -it often appears as the most problematic issue perceived by the public (Ervasti, 1998(Ervasti, , 2012Goul Andersen, 1999;Halvorsen, 2002).…”
Section: Perceptions Of the Mis-targeting Of Welfare Benefitsmentioning
confidence: 99%
“…Those studies invariably show that the European public is relatively critical of not only the performance and outcomes of welfare systems (especially in Southern and Eastern Europe) but also procedural justice: the European public tends to perceive that their countries' welfare systems have relatively high degrees of bureaucracy and low degrees of both efficiency and effectiveness (Roosma et al, 2012). More specifically, studies that examine critical attitudes toward the welfare state conclude that people are most critical about the mis-targeting of welfare benefits in terms of both the abuse and the non-take-up of benefits (Edlund, 1999;Ervasti, 1998Ervasti, , 2012Goul Andersen, 1999;Halvorsen, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Roosma, J. Gelissen, and W. Oorschot, suggest that attitudes towards the dimensions differ between Western/ Northern and Eastern/Southern European welfare states [9,250]. In Western/Northern European countries, respondents are more positive towards the outcomes and efficiency of the welfare state than in Eastern/Southern European countries.…”
Section: Brief Literature Reviewmentioning
confidence: 99%